Mutation analysis in 600 French cystic fibrosis patients. Issue 7 (July 1994) - Chevalier-Porst, F; Bonardot, A M; Gilly, R; Chazalette, J P; Mathieu, M; Bozon, D
Abstract : The cystic fibrosis transmembrane conductance regulator (CFTR) gene of 600 unrelated cystic fibrosis (CF) patients living in France (excluding Brittany) was screened for 105 different mutations. This analysis resulted in the identification of 86% of the CF alleles and complete genotyping of 76% of the patients. The most frequent mutations in this population after delta F508 (69% of the CF chromosomes) are G542X (3.3%), N1303K (1.8%), W1282X (1.5%), 1717-1G–>A (1.3%), 2184delA + 2183 A–>G (0.9%), and R553X (0.8%).